Comparative Analysis using Revit BIM Between Traditional Malay House and Modern House in Natural Daylighting - NOOR HAFIZAH ABDUL GHAPAR; NURDALILA SAJI (Progress in Engineering Application and Technology, 2025)
This research examines how effectively natural lighting is utilized in Traditional Malay Houses in comparison to Modern Houses, focusing on the architectural characteristics that impact light distribution. The aim is to evaluate how these residences capture daylight, especially through different openings such as windows and doors. By employing lux meter measurements, Illuminance Analysis, and Daylight Factor simulations, data was collected from essential areas like living rooms and kitchens. The results indicate that Traditional Malay Houses considerably exceed Modern Houses regarding natural daylight levels, with average lux readings often surpassing 21 lux in spaces such as kitchens and prayer areas. In contrast, Modern Houses frequently recorded lux levels as low as 1 lux, attributed to design choices that restrict daylight entry. The findings illustrate that Traditional Malay Houses considerably excel compared to Modern Houses in attaining higher lux levels, primarily due to the design and materials of traditional windows and doors. These results highlight the necessity of incorporating traditional architectural features into modern designs to improve the use of natural light.